Implementasi Manajemen Sumber Daya Manusia di SMA N 1 Kota Metro - Purwaningsih Purwaningsih (Jurnal Dewantara, 2019)
It is very important for public and private educational institutions and related institutions to make every effort to manage human resources properly. The purpose of this study was to determine: Implementation of human resource management in SMA N 1 Metro City; Obstacle factor; Supporting factors; and Solutions to overcome obstacles regarding the implementation of human resource management in improving the quality of education. Based on the data it can be concluded: The process of implementing human resource management; Awareness, concern for schools, in addition to that ideological issues that make a sense of mutual support and activeness of teachers in transferring knowledge; Until now the management of human resources can still function properly, although it still needs to be improved; and the School provides solutions to existing obstacles by building shared awareness, equalizing goals, establishing a sense of cohesiveness with employees, making a good contribution, always developing employees and students well, as well as having a sense of cooperation between student guardians and the school .